Changes in serum proteins in cats with obesity: a proteomic approach - Cañadas-Vidal, Esmeralda; Muñoz-Prieto, Alberto; Rešetar Maslov, Dina; Rubić, Ivana; González Sánchez, Juan Carlos; Garcia-Martinez, Juan D.; Ceron, José J.; Mrljak, Vladimir; Pardo-Marin, Luis; Martinez-Subiela, Silvia; Tvarijonaviciute, Asta (Animals, 2025)
Obesity is defined as the excessive accumulation of adipose tissue and is currently the most common disease in cats. Similarly to humans, obesity negatively impacts the health and welfare of cats, predisposing them to many other disorders. The objective of this study was to compare the serum proteomes of normal-weight and overweight/obese cats, aiming to gain insights into the physiopathology of feline obesity and potentially identify new biomarkers. For this, serum samples from a total of 20 adult neutered domestic shorthair client-owned cats, ten normal weight and ten overweight/obese, were submitted to tandem mass tags labelling and liquid chromatography-mass spectrometry (LC-MS/MS) analysis. A total of 288 proteins were detected in the serum samples. Out of these, 12 proteins showed statistically significant differences in abundance between control cats and cats with obesity, namely Ig-like domain-containing protein, Alpha-2-HS-glycoprotein, Complement C8 gamma chain, An-tithrombin-III, Serpin family A member 1, Complement factor H, C3-beta-c, Albumin, C4b-binding protein alpha chain, Alpha-1-B glycoprotein, Solute carrier family 12 member 4, and Fibronectin. Overall this report identifies new proteins involved and provides additional knowledge about the physiopathological changes related to feline obesity.
Gesehen am 13.01.2026